Perspektif Mahasiswa BIPA Tiongkok terhadap Budaya Indonesia - Ari Kusmiatun (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
The existence of Indonesian as a foreign language, known as BIPA (Bahasa Indonesia bagi Penutur Asing) is getting more prominence since it has just declared as one of official language at UNESCO on November 20, 2023. This study aims to describe the perspectives of BIPA students from China who participate in the credit transfer program at the Faculty of Languages, Arts, and Culture, Yogyakarta State University, towards Indonesian culture. This research uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation studies of mini project papers. The subjects of this research are 12 foreign students from Yunnan Minzu University (YMU), Quijing Normal University (QJNU), and Beijing Language and Culture University (BLCU). The results show that almost all BIPA students from China have a positive perspective on Indonesian culture. These positive perspectives are seen in various aspects such as slang language, the BIPA learning process, education, marriage, tourism, and national holidays in Indonesia. This study provides a deeper understanding of foreign students' views on Indonesian culture and can enhance the effectiveness of cultural learning in the BIPA program.